The global population structure and evolutionary history of the acquisition of major virulence factor-encoding genetic elements in Shiga toxin-producing Escherichia coli O121:H19. Issue 12 (8th December 2021) - Nishida, Ruriko; Nakamura, Keiji; Taniguchi, Itsuki; Murase, Kazunori; Ooka, Tadasuke; Ogura, Yoshitoshi; Gotoh, Yasuhiro; Itoh, Takehiko; Toyoda, Atsushi; Mainil, Jacques Georges; Piérard, Denis; Seto, Kazuko; et al.
Abstract : Shiga toxin (Stx)-producing Escherichia coli (STEC) are foodborne pathogens causing serious diseases, such as haemorrhagic colitis and haemolytic uraemic syndrome. Although O157:H7 STEC strains have been the most prevalent, incidences of STEC infections by several other serotypes have recently increased. O121:H19 STEC is one of these major non-O157 STECs, but systematic whole genome sequence (WGS) analyses have not yet been conducted on this STEC. Here, we performed a global WGS analysis of 638 O121:H19 strains, including 143 sequenced in this study, and a detailed comparison of 11 complete genomes, including four obtained in this study. By serotype-wide WGS analysis, we found that O121:H19 strains were divided into four lineages, including major and second major lineages (named L1 and L3, respectively), and that the locus of enterocyte effacement (LEE) encoding a type III secretion system (T3SS) was acquired by the common ancestor of O121:H19. Analyses of 11 complete genomes belonging to L1 or L3 revealed remarkable interlineage differences in the prophage pool and prophage-encoded T3SS effector repertoire, independent acquisition of virulence plasmids by the two lineages, and high conservation in the prophage repertoire, including that for Stx2a phages in lineage L1. Further sequence determination of complete Stx2a phage genomes of 49 strains confirmed that Stx2a phages in lineage L1 are highly conserved short-tailed phages, while those in lineage L3 are long-tailed lambda-like phages with notable genomic diversity, suggesting that an Stx2a phage was acquired by the common ancestor of L1 and has been stably maintained. Consistent with these genomic features of Stx2a phages, most lineage L1 strains produced much higher levels of Stx2a than lineage L3 strains. Altogether, this study provides a global phylogenetic overview of O121:H19 STEC and shows the interlineage genomic differences and the highly conserved genomic features of the major lineage within this serotype of STEC.